Optimization of Particle Size and Addition of Vinasse Waste to Improve Characteristics of Rice Husk Charcoal Briquettes - Santi, Sintha Soraya; Azzahra, Tsania Putri; Salfana, Dian Rizka; Pasang, Timotius (CHEESA: Chemical Engineering Research Articles, 2024)
Biobriquettes are a biomass fuel with high calorific value. This study aims to determine the optimal conditions for the particle size of husk charcoal and the addition of vinasse waste as an independent variable, using the Response Surface Methodology and the Central Composite Design (CCD) method on Design Expert 13 software. The sample mixed with tapioca starch (8:1), which acts as an adhesive, and add vinasse waste in 3, 6, 9, and 12 mL amounts. Carbonization process, which is then mashed and sieved according to particle sizes of 20, 30, 40, 50, and 60 mesh. Then, the sample is mixed with tapioca starch as adhesive with the ratio of charcoal and adhesive 8:1 as well as vinasse waste in volumes of 3, 6, 9, and 12 mL. The resulting briquette samples were tested in the form of water content, ash content, and calorific value tests. The optimum conditions that have a significant effect on the response variable are the combination of particle size variables of 35.152 mesh and the volume of vinasse waste of 6.049 mL. The moisture content obtained was 6.696%., The ash content was 5.450%, and the calorific value was 5003.399 cal/g with a desirability value of 0.927 in the quadratic model.